An integrated approach for improving energy efficiency of manufacturing process chains. Issue 1 (2nd January 2016) - Mousavi, Smaeil; Thiede, Sebastian; Li, Wen; Kara, Sami; Herrmann, Christoph
Abstract : The rising energy prices and increasingly imposing regulations have drawn attention for improving the energy efficiency of manufacturing processes. Over the past decade, different approaches have been developed to target from individual unit processes to entire manufacturing systems. However, each model or approach has limitations in terms of the efficiency improvement. Thus, an integrated approach is proposed to overcome these limitations combining unit process energy consumption models with production system simulation. The outcome potentially leads to a more energy-efficient production and process planning, which considers the dynamics of individual processes as well as the entire system. Two case studies are presented to demonstrate the approach and its benefits.